1999
DOI: 10.1116/1.591008
|View full text |Cite
|
Sign up to set email alerts
|

Moving boundary transport model for acid diffusion in chemically amplified resists

Abstract: Polymer structure effect on dissolution characteristics and acid diffusion in chemically amplified deep ultraviolet resists J.We propose a general model for latent image formation in chemically amplified resists. The model is based on a moving boundary acid transport concept that incorporates transient free volume generation and densification. It is based on experimental observation of negligible acid diffusion in polyhydroxysterene below T g . The model offers insight into the post exposure bake ͑PEB͒ reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…The evaporation of the solvent generates transient free volume in the polymer film during the soft bake and post-exposure bake steps. 5 The bake temperatures were below the glass transition temperature of the polymer film. Glassy polymers do not respond immediately to a change in their equilibrium state.…”
Section: Discussionmentioning
confidence: 99%
“…The evaporation of the solvent generates transient free volume in the polymer film during the soft bake and post-exposure bake steps. 5 The bake temperatures were below the glass transition temperature of the polymer film. Glassy polymers do not respond immediately to a change in their equilibrium state.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the reaction-diffusion models involve both reaction and diffusion mechanisms [7][8][9][10][11]. Third, the moving boundary transport models include the volatility of deprotection by-products and the relaxation of free volume [12,13]. Among the three PEB models, the moving boundary transport model is the most general and complicated one.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three PEB models, the moving boundary transport model is the most general and complicated one. The reaction-diffusion model and the diffusionless model may be considered special cases of the moving boundary transport model [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the acid is subsequently trapped in the deprotected polymer matrix leading to a net reduction in the available acid for deprotection. Numerical calculations based upon this model show that the reaction front propagates as a sharply defined interface into the protected polymer layer [14]. Other successful modeling approaches include the use of a simulation incorporating in detail the deprotection reaction kinetics as well as diffusion mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between the models largely lie in the description of the acid diffusion process and the detail in which the reaction kinetics are incorporated. Predictions from reaction-diffusion models have been compared with the total extent of reaction with FTIR data before development in several systems [7,8,[12][13][14]. Top loss deprotection experiments and comparison with different acid diffusion descriptions showed that Fickian diffusion cannot explain the experimental results [11].…”
Section: Introductionmentioning
confidence: 99%